ANALYSIS OF THE HORIZONTAL STRUCTURE OF THE YOUNG REGENERANT BANK IN A DEGRADED RIVERSIDE ECOSYSTEM IN THE SEMIARID OF PARAIBA - Silva, Geneilson Evangelista da; Barbosa, Francisca Maria; de Lacerda, Alecksandra Vieira (Floresta, 2023)
The objective was to evaluate the structure of the young regenerating stratum in a degraded riverside area of caatinga in the Serra Branca-PB, the semiarid region of Paraíba. Two inventories were performed, one in the dry season (September/2019) and the other in the rainy season (March/2020). In the riparian area, 50 contiguous plots of 10 X 20 m were allocated. In the center of each plot, subplots of 1 X 1 m were plotted, totaling 50 m2, for the evaluation of the regenerating stratum. The density, frequency, dominance, and importance value parameters were calculated. The heterogeneity of the floristic community was determined by the Shannon diversity index (H’) and Pielou’s evenness index (J’). In both inventories, 39 species distributed in 31 genera and 14 families were recorded. In the dry period, the species with the highest importance value were respectively Alternanthera tenella Colla, Sida galheirensis Ulbr. and Fabaceae 1. Related to the rainy season, the species with the highest importance value were Urochloa decumbens (Stapf), R.D.Webster, Blainvillea acmella (L.), Philipson, and Boerhavia diffusa L. The diversity and evenness values were 1.22 nats.ind.-1 and 0.49 (dry season) and 2.59 nats.ind.-1 and 0.71 (rainy season), respectively. The results obtained in the two inventories were similar to other studies in these same conditions of degraded caatinga. The study also demonstrated that this area is in an initial stage of ecological succession, with a predominance of exotic species in both inventories (dry and rainy).